Kekuatan Tarik dan Impak Komposit Matrik Polimer Serat Kulit Durian dengan Variasi Perlakuan Alkalisasi (NaOH, NaOH+H2O2, dan KOH) Serat - badri, muftil; Chaerunissa, Andini; Dalil, M.; Saputra, Sukemi Indra (Rekayasa Material, Manufaktur dan Energi, 2025)
Durian fruit is one of the most popular fruits in Indonesia. Half of the durian fruit is the peel, which produces a lot of waste. The durian peel is not useful and also has no economic value. Durian peel contains fibers that have the potential to be utilized. The utilization of durian peel fiber as a composite natural fiber is an effort to reduce waste from the peels. Improvement of the properties of durian peel fibers can be applied by alkali treatment of the fibers. The purpose of this study is to obtain the cellulose content, tensile strength and impact toughness of durian peel fiber reinforced polymer composites by varying the alkali treatment of the fibers. The volume fraction of fiber and matrix composite was used 50:50. This study varied 0% alkali, fiber alkali as follows: 5% NaOH, 5% NaOH + 3% H2O2, 5% KOH. The results showed the highest cellulose content of 59.48% in the 5% NaOH + 3% H2O2 treatment. It was found that the optimum tensile strength was 8.58 MPa in the 5% NaOH + 3% H2O2 fiber treatment. The highest impact toughness of 2.8 kJ/m2 was obtained in 0% alkali treatment of fiber composite.